Water as a morphogen in landscapes = L'eau comme morphogène dans les paysages : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). - Robert, Sandrine,; Sittler, Benoit, (Archaeopress archaeology., 2016)
Water as generator of networks was the core topic of the second session organized by the commission Theory and Methods in Landscape Archaeology: Archeogeography that began in 2011 on occasion of the Florianopolis Congress.